حقوق الامتياز الخاصة الواردة على العقار في القانون المدني الجزائري - ورخ, نور الدين (جامعة الوادي University of Eloued, 2017)
إن انتهاج الدولة لسياسة الاقتصاد الحر وتحرير التعاملات الاقتصادية بين الأفراد، قصد تشجيع سوق التعاملات العقارية فيما بينهم من أجل منح الثقة والائتمان في هذه المبادلات، وهذا من خلال إعطاء الدائن الحماية القانونية اللازمة، فالمشرع قد نص ونظم أحكام التأمينات العينية ضمن الكتاب الرابع من القانون المدني ومن بين هذه التأمينات حقوق الامتياز الخاصة الواردة على العقار. فهي حقوق عينية تخول لصاحبها سلطة مباشرة يقررها القانون لأصحاب الديون الممتازة، مراعاة منه لصفات ديونهم، وهي تقع على عقار أو عدة عقارات معينة من عقارات المدين، وتخول للدائن أن يتقدم على غيره من الدائنين في استيفاء حقه من ثمن العقار في أي يد يكون. ولقد نص المشرع ضمن القانون المدني على ثلاث أنواع من حقوق الامتياز العقارية، امتياز بائع العقار المادة(999)، امتياز متقاسمي العقار المادة(1001) وكذلك امتياز المقاولين والمهندسين المعماريين المادة (1000). وفي حال نشأت هذه الحقوق مستوفية لجميع الشروط القانونية الواجب توافرها، ولكي تكون نافذة بين أطرافها وفي مواجهة الغير فلا بد من قيدها لدى المحافظة العقارية التي يقع ضمن اختصاصها موقع العقار محل الامتياز وفقا للإجراءات المحددة في قانون الشهر العقاري، وهذا ما يترتب عليه العديد من الآثار حيث تمنح لصاحب الدين الممتاز حق التتبع والأفضلية، بيد أن حقوق الامتياز العقارية تنقضي مثلها مثل باقي الحقوق العينية التبعية، فتنقضي بصفة أصلية أي مستقلة عن الدين الممتاز، أو تنقضي بصفة تبعية تبعا لانقضاء هذا الدين. The state has adopted the policy of the free economy in liberalizing economic transactions between individuals, in order to encourage real estate market transactions between them in order to give confidence and credit in these exchanges, this provide the necessary judicial protection To the creditors, the legislator has enacted and organized the provisions of the actual security in the book four civil code, among these security the special privileges real estate. These are real rights which give to the owners the direct authority granted by law to the owners of the debts privileges, taking into account their characteristics, it places on one or several buildings of the debtor, they grant to the creditor the right of preference against the others Creditors of the return price of such immovable's. The legislature enacted three types of property rights, the seller's privilege of an immovable (999), the privilege of the contractor and the architects (1000), and the privilege of the coparterant of a building (1001). In the case of these rights, they arise and meet all the legal requirements to be respected, for which it is possible to oppose between these parties and the third parties, it must be inscribed at the level of the competent land conservation according to the procedures and the formalities of the This is what implies several effects, give to the creditor privileges the right of preference and so on, however, the rights of real estate privileges are extinguished like the other real rights incidental, the rights of special privileges are extinguished Independent of the claim, or are extinguished depending on the extinguishment of the claim.
قانون عقاري
Keywords: التعاملات العقارية –الائتمان –الدائن -التأمينات العينية - القانون المدني - حقوق الامتياز الخاصة الواردة على العقار -امتياز بائع العقار -امتياز متقاسمي العقار -امتياز المقاولين والمهندسين المعماريين – القيد –حق التتبع –حق التقدم; - -real estate insurance – credit - creditors - civil Code - Special real estate privileges - Privilege of seller of building - Privilege of entrepreneurs and architects - Privilege of the coparterant of a building – registration - resale right - right of preference.